KAJIAN FILOLOGIS TERHADAP NASKAH WAWACAN SAJARAH HAJI MANGSUR - EVA SYARIFAH WARDAH (Al Qalam, 2011)
Wawacan Sajarah Haji Mangsur (WSHM) is one of historical literature works telling about the stories of Banten in the sultanate period in which Haji Mangsur becomes the main actor in this Wawacan. There are three manuscripts of WSHM which can be inventarized; two of them are collected in Bibliotthek Library of Leiden University, the Netherlands, indicated by the code LOr. 7420 dan LOr.7419, and another one is placed in National Libary of Jakarta indicated by the code BG.183. All of these three manuscripts are generally hand-writing by using Arab-Pegon text in Javanese Banten language. After identifying and analyzing the text, it seems that these three manuscripts derives from one source. Based on the result of comparing the texts, all of them are used in the text edition. After criticizing the text, there are several writing error on the WHSM text,i.e. in the form of substitution, addition, and lacuna. Such errors are ,then, corrected in the text edition. Reading materials on the base manuscript which is corrected by substituting, rediuing, or adding are noted in critical apparatus. The method of text edition used in this study is the basis method. It is used because among all these three manuscripts is a manuscript, indicated by the code LOr. 7420, which takes the shine of from the other ones. Key Words: The Manuscript of Wawacan Haji Mangsur, Philology, Text Edition